PENGARUH PROFITABILITAS, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN (STUDI KASUS PADA PERUSAHAAN SEKTOR ENERGI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021-2023) - Athena, Maria Eliza; Basri, Yesi Mutia; Hanif, Rheny Afriana (LPPM Universitas Bina Bangsa, 2025)
This research is a quantitative study that aims to determine the effect of profitability, capital structure, and company size on firm value in the energy sector listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The sample in this study, namely energy sector companies, was taken using purposive sampling technique so that 44 samples were obtained that met the criteria for 3 years. Data analysis was carried out using descriptive analysis, classical assumption test, multiple linear regression analysis and hypothesis testing with SPSS 30.0. The results showed that profitability, capital structure, and company size have an effect on firm value.